Thomson scattering and collisional ionization in the X-ray grating spectra of the recurrent nova U Scorpii - Orio, M. (2013)
We present a Chandra observation of the recurrent nova U Scorpii, done with the High Resolution camera-S (HRC-S) detector and the Low Energy Transmission Grating (LETG) on day 18 after the observed visual maximum of 2010, and compare it with XMM?Newton observations obtained on days 23 and 35 after maximum. The total absorbed flux was in the range 2.2?2.6 × 10−11 erg cm−2 s−1, corresponding to unabsorbed luminosity 7?8.5 × 1036 ×(d/12 kpc)2 for N(H) = 2?2.7 × 1021 cm−2. On day 18, 70 per cent of the soft X-tray flux was in a continuum typical of a very hot white dwarf (WD) atmosphere, which accounted for about 80 per cent of the flux on days 23 and 35. In addition, all spectra display very broad emission lines, due to higher ionization stages at later times. With Chandra we observed apparent P Cygni profiles. We find that these peculiar profiles are not due to blueshifted absorption and redshifted emission in photoionized ejecta, like the optical P Cyg of novae, but they are rather a superposition of WD atmospheric absorption features reflected by the already discovered Thomson scattering corona, and emission lines due to collisional ionization in condensations in the ejecta. On days 23 and 35, the absorption components were no longer measurable, having lost the initial large blueshift that displaced them from the core of the broad emission lines. We interpret this as an indication that mass-loss ceased between day 18 and day 23. On day 35, the emission line spectrum became very complex, with several different components. Model atmospheres indicate that the WD atmospheric temperature was about 730 000 K on day 18 and reached 900 000?1000 000 K on day 35. This peak temperature is consistent with a WD mass of at least 1.3 M⊙.